Effectiveness of Activated Carbon from Corn Cobs (Zea mays L.) as an Adsorbent for Methylene Blue Dyes - Henry Fonda Aritonang; Fajar Saut Hamonangan Sitinjak; Audy Denny Wuntu; Harry Julius Koleangan; Widya Astuti Lolo (Jurnal Ilmiah Sains, 2025)
Wastewater treatment is one of the methods used to reduce pollution levels and the harmful effects of wastewater on the environment and human health. Wastewater containing dye substances also has the potential to kill organisms living in the surrounding environment. One solution for treating synthetic wastewater is through the adsorption process. The adsorbent used is derived from corn cobs (Zea mays L.), so the aim of this study is to synthesize and evaluate activated carbon from corn cobs as an adsorbent for methylene blue (MB). To achieve this, the pyrolysis method was employed by placing corn cobs in a furnace heated to 600 °C for 3 hours. The resulting activated carbon was then treated with either H₂SO₄ or NaOH for activation.The produced activated carbon was characterized using X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscope-Energy Dispersive Spectrometry (SEM-EDS) to analyze its crystal structure, functional groups, morphology, and elemental composition. Characterization results revealed that the activated carbon had a small crystallite size and irregular pores. Adsorption tests using a UV-Vis Spectrophotometer demonstrated that corn cob-based activated carbon efficiently adsorbed MB. The highest adsorption efficiency was achieved at a contact time of 90 minutes (99.03%), pH 7 (99.01%), and a concentration of 50 ppm (99.17%) using 0.1 grams of adsorbent. Adsorption isotherm analysis indicated that the process followed the Freundlich isotherm model, suggesting multilayer adsorption on a heterogeneous adsorbent surface. Keywords: Adsorbent; activated carbon; methylene blue; sodium hydroxide; corn cobs